IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER DISIPLIN DALAM PROSES PEMBELAJARAN PPKn - Pittriyani Pittriyani; Endang Purwaningsih; Rum Rosyid (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine how to implement the strengthening of disciplinary character education in the PPKn learning process in class X IPS 3 SMAN 5 Pontianak Utara. The research method used is descriptive with a qualitative form of research approach. Sources of data in this study were PPKn teachers and 6 students of class X IPS 3 SMAN 5 Pontianak Utara. Data collection techniques used in this study are observation techniques, interview techniques, documentary study techniques, with data collection tools used are observation sheets, interview sheets, and documentaries. The data analysis techniques used were data reduction, data display, and conclusion drawing. The results of this study are that the teacher and the school have implemented the character of discipline in school and in the classroom during the learning process, but there are still students who do not obey the rules or agreements made by teachers and students at the beginning of learning. The factors that cause students to violate rules or agreements are internal factors such as lazy students, everything they want is instant, as well as family problems, and external factors such as the number of students who are too large so that teachers cannot optimally manage the class, and the lack of supporting facilities in learning. Various efforts have been made by the teacher, starting from giving admonitions, warnings, advice, direction, and approaching students, as well as applying sanctions or penalties to students who violate rules or agreements. Keywords: Discipline, Implementation, Strengthening Character Education.